2013 IEEE Power &Amp; Energy Society General Meeting 2013
DOI: 10.1109/pesmg.2013.6672226
|View full text |Cite
|
Sign up to set email alerts
|

Power losses minimization within Spanish wind farms evacuation networks

Abstract: The aim of this paper is to evaluate the influence on power losses of the provision of voltage control by wind farms within the grid that connects them to the transmission network. In addition, the paper estimates the economic profit or cost that this technology could obtain in case of providing voltage control. This paper concentrates on the Spanish situation, where wind farms are connected to the transmission network by an evacuation network without containing loads. Thus, from the economic point of view, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, they demonstrated that DFIG is able to minimize the loss for various reactive power designs. Saiz-Marin et al [19] assessed the impact of power loss due to expanding voltage control in a grid connecting wind farms to the transmission network, and the benefits and costs which extend from developing voltage control. Lumbreras and Ramos [20] utilized mixed integer programming and decomposition strategies for optimally designing offshore wind farm layouts (OWLs) considering such constraints as transformer and redundant cables requirements.…”
Section: Power Lossmentioning
confidence: 99%
“…Moreover, they demonstrated that DFIG is able to minimize the loss for various reactive power designs. Saiz-Marin et al [19] assessed the impact of power loss due to expanding voltage control in a grid connecting wind farms to the transmission network, and the benefits and costs which extend from developing voltage control. Lumbreras and Ramos [20] utilized mixed integer programming and decomposition strategies for optimally designing offshore wind farm layouts (OWLs) considering such constraints as transformer and redundant cables requirements.…”
Section: Power Lossmentioning
confidence: 99%